Regional Cerebral Oximetry as an Indicator of Acute Brain Injury in Adults Undergoing Veno-Arterial Extracorporeal Membrane Oxygenation–A Prospective Pilot Study - Khan, Imad; Rehan, Mehboob; Parikh, Gunjan; Zammit, Christopher; Badjatia, Neeraj; Herr, Daniel; Kon, Zachary; Hogue, Charles; Mazzeffi, Michael (Frontiers in Neurology, 2018)
Background: Regional cerebral oxygen saturation (rScO2) measured by near-infrared spectroscopy (NIRS) can be used to monitor brain oxygenation in extracorporeal membrane oxygenation (ECMO). ECMO patients that develop acute brain injuries (ABIs) are observed to have worse outcomes. We evaluated the association between rScO2 and ABI in venoarterial (VA) ECMO patients. Methods: We retrospectively reviewed prospectively-collected NIRS data from patients undergoing VA ECMO from April 2016 to October 2016. Baseline demographics, ECMO and clinical characteristics, cerebral oximetry data, neuroradiographic images, and functional outcomes were reviewed for each patient. rScO2 desaturations were defined as a >25% decline from baseline or an absolute value < 40% and quantified by frequency, duration, and area under the curve per hour of NIRS monitoring (AUC rate, rScO2*min/h). The primary outcome was ABI, defined as abnormalities noted on brain computerized tomography (CT) or magnetic resonance imaging (MRI) obtained during or after ECMO therapy. Results: Eighteen of Twenty patients who underwent NIRS monitoring while on VA ECMO were included in analysis. Eleven patients (61%) experienced rScO2 desaturations. Patients with desaturations were more frequently female (73 vs. 14%, p = 0.05), had acute liver dysfunction (64 vs. 14%, p = 0.05), and higher peak total bilirubin (5.2 mg/dL vs. 1.4 mg/dL, p = 0.02). Six (33%) patients exhibited ABI, and had lower pre-ECMO Glasgow Coma Scale (GCS) scores (5 vs. 10, p = 0.03) and higher peak total bilirubin levels (7.3 vs. 1.4, p = 0.009). All ABI patients experienced rScO2 desaturation while 42% of patients without ABI experienced desaturation (p = 0.04). ABI patients had higher AUC rates than non-ABI patients (right hemisphere: 5.7 vs. 0, p = 0.01, left hemisphere: 119 vs. 0, p = 0.06), more desaturation events (13 vs. 0, p = 0.05), longer desaturation duration (2:33 vs. 0, p = 0.002), and more severe desaturation events with rScO2 < 40 (9 vs. 0, p = 0.05). Patients with ABI had lower GCS scores (post-ECMO initiation) before care withdrawal or discharge than those without ABI (10 vs. 15, p = 0.02). Conclusions: The presence and burden of cerebral desaturations noted on NIRS cerebral oximetry are associated with secondary neurologic injury in adults undergoing VA ECMO.